Openness In Psychotherapy: Late Heidegger And The Clearing (Existential Analysis: Journal of the Society for Existential Analysis, 2018)
Readily acknowledged but rarely understood, Openness, as a concept in psychotherapy, invites further attention. This paper takes philosophy as its starting point and continues by exploring the writings of therapists from across the spectrum of modalities. It also incorporates recent, personal research in order to elucidate a therapeutic understanding of Openness. This review into Openness begins with an image: Heidegger's forest clearing (die Lichtung), his metaphor for the Openness of Being. Following on from this, the subject is approached through a series of descriptions: the nature of Self, therapeutic presence and similarities between Openness and mindfulness. At the same time, the paper acknowledges the difficulties experienced by therapist when staying-with the anxiety evoked by Openness. In short, this paper sheds light on how therapists embody Openness in their work.
Keywords: Openness; the clearing (die Lichtung); Gelassenheit; not-knowing; anxiety; aletheia; mindfulness; phenomenology